Is there a role for pyloric exclusion after severe duodenal trauma? - Cruvinel Neto,José (2014)
Duodenal trauma is an infrequent injury, but linked to high morbidity and mortality. Surgical management of duodenal injuries is dictated by: patient's hemodynamic status, injury severity, time of diagnosis, and presence of concomitant injuries. Even though most cases can be treated with primary repair, some experts advocate adjuvant procedures. Pyloric exclusion (PE) has emerged as an ancillary method to protect suture repair in more complex injuries. However, the effectiveness of this procedure is debatable. The "Evidence Based Telemedicine - Trauma & Acute Care Surgery" (EBT-TACS) Journal Club performed a critical appraisal of the literature and selected three relevant publications on the indications for PE in duodenal trauma. The first study retrospectively compared 14 cases of duodenal injuries greater than grade II treated by PE, with 15 cases repaired primarily, all of which penetrating. Results showed that PE did not improve outcome. The second study, also retrospective, compared primary repair (34 cases) with PE (16 cases) in blunt and penetrating grade > II duodenal injuries. The authors concluded that PE was not necessary in all cases. The third was a literature review on the management of challenging duodenal traumas. The author of that study concluded that PE is indicated for anastomotic leak management after gastrojejunostomies. In conclusion, the choice of the surgical procedure to treat duodenal injuries should be individualized. Moreover, there is insufficient high quality scientific evidence to support the abandonment of PE in severe duodenal injuries with extensive tissue loss.